Moderate to Severe Multifidus Fatty Atrophy is the Risk Factor for Recurrence After Microdiscectomy of Lumbar Disc Herniation - Fengzhao Zhu; Dongqing Jia; Yaqing Zhang; Ya Ning; Xue Leng; Chencheng Feng; Changqing Li; Yue Zhou; Bo Huang (Neurospine, 2023)
Objective We attempted to investigate the potential risk factors of recurrent lumbar disc herniation (rLDH) after tubular microdiscectomy. Methods We retrospectively analyzed the data of patients who underwent tubular microdiscectomy. The clinical and radiological factors were compared between the patients with and without rLDH. Results This study included 350 patients with lumbar disc herniation (LDH) who underwent tubular microdiscectomy. The overall recurrence rate was 5.7% (20 of 350). The visual analogue scale (VAS) score and Oswestry Disability Index (ODI) at the final follow-up significantly improved compared with those preoperatively. There was no significant difference in the preoperative VAS score and ODI between the rLDH and non-rLDH groups, while the leg pain VAS score and ODI of the rLDH group were significantly higher than those of the non-rLDH group at final follow-up. This suggested that rLDH patients had a worse prognosis than non-rLDH patients even after reoperation. There were no significant differences in sex, age, body mass index, diabetes, current smoking and drinking, disc height index, sagittal range of motion, facet orientation, facet tropism, Pfirrmann grade, Modic changes, interdisc kyphosis, and large LDH between the 2 groups. Univariate logistic regression analysis revealed that rLDH was associated with hypertension, multilevel microdiscectomy, and moderate-severe multifidus fatty atrophy (MFA). A multivariate logistic regression analysis indicated that MFA was the sole and strongest risk factor for rLDH after tubular microdiscectomy. Conclusion Moderate-severe MFA was a risk factor for rLDH after tubular microdiscectomy, which can serve as an important reference for surgeons in formulating surgical strategies and the assessment of prognosis.